Meta-Analysis of The Effectiveness of The Flipped Classroom Model On Students’ HOTS in Mathematics - Pujiriyanto; Handaru, Calista; Hukom, Julham (JTP - Jurnal Teknologi Pendidikan, 2024)
The use of the Flipped Classroom (FC) Model has become a global phenomenon in the last decade, and has had a significant impact on mathematics learning objectives. Nevertheless, the scientific literature shows inconsistent results in testing the underlying theoretical assumptions in this model. This meta-analysis study collected analyses of 42 effect sizes from 31 journal articles and international proceedings between 2014 and 2024. The Comprehensive Meta-Analysis (CMA) program was used as a calculation tool, with the Hedges coefficient used to calculate the effect size at a 95% confidence level. The results of analysis using the random-effect estimation model show that the overall effect size is 1.06 (large effect category). This shows that the use of the FC model has a relatively high positive influence on High Order Thinking Skills (HOTS) mathematics when compared to the conventional model. In addition, analysis of research characteristics shows that the effectiveness of using the FC model can be increased by considering factors such as the type of platform used, the type of FC model applied, educational level, and the capacity of the experimental class. These findings provide valuable guidance for educators in the future use of the FC model, particularly in developing students’ mathematics HOTS. Keywords: Flipped Classroom; HOTS, Mathematics; Meta-Analysis; Effect Size